Characterization of draw solution in forward osmosis process for the treatment of synthetic river water - Yeo, Ryan Whye Seong (2014)
Forward osmosis is a process that depends on the concentration gradient and also osmotic potential to treat water which is currently, applicable in many industries. The main factor which affects the entire process of forward osmosis is the draw solution as draw solution acts as the driving force which drives water to past through semi-permeable membrane by means of concentration gradient. This research focuses on the characterization of draw solution in order to provide the optimum effect in treating river water in Malaysia. Apart from that, this research used synthesized river water which consists of 15mg/L of humic acid to replace river water as feed solution. This research was done so as to fill the inadequate amount of research done on forward osmosis where river water was used as feed solution. This research was conducted based on two parameters which will impact the water flux and performance of draw solution namely, concentration of draw solution and also osmotic pressure of draw solution. Thus, 4 different draw solutions made up of inorganic salt, fertilizers and organic salts were tested based on 5 different concentrations. This research also measures the humic acid rejection for each draw solution by using UV-vis spectrometer. Besides, reverse salt diffusion caused by different draw solution was also tested in terms of conductivity to determine the best performing draw solution. This research was conducted by using polyamide coated ultrafiltration membrane to separate the feed and draw solution and the permeation module was constructed as the preliminary laboratory work. Based on the results obtained, increase in molarity of draw solution is proportional to the increase in flux of water. The water flux obtained by using related formula showed the highest figure with calcium nitrate at 2.7 x 10^-4 m3/m2.s at 1mol/L, whereas the lowest flux obtained was by fructose with the reading of 2.529 x 10^-05 m3/m2.s. Besides that, calculation shows that the increase in draw solution concentration causes a decrease in humic acid rejection. However, the data recorded showed that every draw solutions at concentrations of 0.1mol/L to 1mol/L have good humic acid rejection at approximately 100%. On the other hand, sodium chloride showed higher reverse salt diffusion than calcium nitrate and the value of reverse salt diffusion increases as the molarity increases. Based on the discussions, it is found that this research showed calcium nitrate at 1mol/L as the best performing draw solution in treating river water. This research can further assist future research on forward osmosis of treating river water by narrowing down the type of draw solution that can provide best efficiency in treating river water and also show the category of draw solution which provides best efficiency.